Réponses

  • Utilisateur Brainly
2013-03-04T21:49:52+01:00

comme cos(a+b)=cosacosb-sinasinb on a cos(a-b)=cos(a+(-b))=cosacos(-b)-sinasin(-b)

or cos(-b)=cosb et sin(-b)=-sinb donc cos(a-b)=cosacosb+sinasinb

 

sin(a-b)=cos(pi/2-(a-b)=cos(pi/2-a+b)=cos(pi/2-a)cosb-sin(pi/2-a)sinb

mais cos(pi/2-a)=sina et sin(pi/2-a)=cosa

donc sin(a-b)=sinacosb-sinbcosa

 

d'où sin(a+b)=sin(a-(-b))=sinacos(-b)-sin(-b)cosa mais cos(-b)=cos(b) et sin(-b)=-sinb

donc sin(a+b)=sinacosb+sinbcosa

et si a=b sin2a=2sinacosa

de même cos(a+a)=cos(2a)=cos²a-sin²a=2cos²a-1=1-2sin²a

 

sin(x+pi/4)=(V2/2)sinx+(V2/2)cosx donc V2sin(x+pi/4)=sinx+cosx

fonction croissante sur -pi/4,pi/4 et valant V2 en x=pi/4